Development Committee : The Managing Director's Written Statement October 2020. (Policy Papers; Policy Paper ;, 2020)
The global economy is embarking on a lengthy path to recovery with modest growth expected for 2021, after a severe contraction this year. The global forecast is subject to unusually large risks. Emerging markets and developing economies face an uphill battle. Low-income developing countries are in an especially vulnerable position and risk a persistent and significant deterioration in development prospects. Controlling the pandemic and cushioning the impact on the economy are key. LIDCs should adopt targeted containment measures and strictly prioritize spending and refrain from policies that could create long term damage. Multilateral cooperation and extensive support from the international community are indispensable. The IMF has helped EMDEs through emergency lending and debt service relief. Targeted surveillance and capacity development will tackle new policy challenges and react nimbly to the needs of the membership including fragile and small states.